Creating a common language: defining individualized, personalized and precision prevention in public health. (20th April 2018) - Bíró, K; Dombrádi, V; Jani, A; Boruzs, K; Gray, M
Abstract: Background: Because of the limited success of population-based prevention methods and due to developments in genomic screening, public health professionals and health policy makers are increasingly interested in more individualized prevention strategies. However, the terminology applied in this field is still ambiguous and thus has the potential to create misunderstandings. Methods: A narrative literature review was conducted to identify how individualized, personalized and precision prevention are used in research papers and documents. Based on the findings a set of definitions were created that distinguish between these activities in a meaningful way. Results: Definitions were found only for precision prevention, not for individualized or personalized prevention. The definitions of individualized, personalized and precision medicine were therefore used to create the definitions for their prevention counterparts. By these definitions, individualized prevention consists of all types of prevention that are individual-based; personalized prevention also consists of at least one form of -omic screening; and precision prevention further includes psychological, behavioral and socioeconomic data for each patient. Conclusions: By defining these three key terms for different types of individual-based prevention both researchers and health policy makers can differentiate and use them in their proper context.